A handbook (Switzerland, 2009)
This handbook describes indicators that can be used to assess, monitor and evaluate the availability, use and quality of Emergency Obstetric Care. These emergency obstetric care indicators can be used to measure progress in a programmatic continuum: from the availability of and access to emergency obstetric care to the use and quality of those services.
Keywords: Obstetrical emergencies,Emergency medical services,Cấp cứu sản khoa,Dịch vụ cấp cứu y tế